The Role of Mbkm in Improving MSME Performance Through Financial Literacy and Digital Marketing in Ketanireng Village, Prigen District, Pasuruan Regency: Peran MBKM dalam Peningkatan Kinerja UMKM Melalui Literasi Keuangan dan Digital Marketing di Desa Ketanireng Kecamatan Prigen Kabupaten Pasuruan - Sriyono; Sugiarto, Herri; Dearelsa, Ghina Balqis; Anisyah, Dewi; Islakhudin, Fatwa Nur Askhab (Procedia of Social Sciences and Humanities, 2022)
This research is motivated by a decrease in income since the Covid-19 pandemic in 2020 so that the condition of MSME actors in Ketanireng Village, Prigen District has decreased. Therefore, in this digital era, information technology can be formed, especially in the field of financial literacy, which is widely used to assist the public in accessing buying and selling products and various financial literacy services. Product marketing through online media is considered very effective because all of its activities can be carried out at any time and can be accessed by all levels of society. This research is a qualitative research descriptive. This study aims to add insight to business actors on the importance of financial literacy because MSMEs have a very important role for economic growth in Ketanireng Village, Prigen District. The results of this study indicate that with the digitalization of marketing such as making Instagram, Facebook, and advertising can promote marketing in the current era of digital technology.